Evaluation of Regression in Epicardial Adipose Tissue Thickness on Cardiac MRI in Post-Acute Coronary Syndrome Patients - Syed, Syed Sajiddain; Khan, Muhammad Nadir; Chauhdry, Azhar Ali; Ghous, Muhammad Waleed; Ali, Gulzar (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate changes in epicardial adipose tissue (EAT) on cardiac magnetic resonance imaging (CMRI) in patients treated for acute coronary syndrome (ACS) and to assess its association with the severity of coronary artery disease (CAD).Study Design: Prospective longitudinal study.Place and Duration of Study: Cardiology Department of Armed Forces Institute of Cardiology, National Institute of Heart Diseases, Rawalpindi, Pakistan; from Aug 2025 to Nov 2025.Methods: Overall, 102 ACS patients aged 18–65 years, underwent both PCI and cardiac magnetic resonance imaging (CMR) were enrolled through consecutive sampling. Prior CABG patients, patients with LVEF